The Role of Imports for Exporter Performance in Peru - Pierola, Martha Denisse; Fernandes, Ana Margarida; Farole, Thomas (World Bank, Washington, DC, 2015)
Using highly disaggregated firm-level customs transaction data for imports and exports in Peru over the 2000–2012 period, this paper explores the relationship between imports of intermediate inputs and firm export performance. The paper shows that greater use, variety, and quality of imported intermediate inputs is significantly correlated with higher exports, faster export growth, greater diversification of export markets, and higher quality exports (as measured by relative unit prices) at the firm level. This relationship is robust and persistent to controls for unobserved firm heterogeneity and year fixed effects. The use of imported inputs is also associated with higher productivity at the firm level. Considering the relationship between specific trade policy measures and the import performance of those exporters that are direct importers, the analysis shows that those exposed to higher tariffs and nontariff measures import less in total and exhibit lower import variety. The use of the advanced clearance procedure as the modality to clear customs for imports is favorable to the import performance of exporter-importers, in that the users of the modality import more and import a more diversified bundle of inputs than those that do not use it, even after controlling for firm size.